Studi Literatur: Penanaman Sikap Anti Bullying Verbal Melalui Pembelajaran IPS - Damayanti, Ni Luh Rani (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to determine the phenomenon of verbal bullying, both directly and through social media, affecting the development of students' character and the dynamics of social interaction in the educational environment; to find out that social studies learning can be integrated effectively to instill anti-verbal bullying values in students and to find out the learning methods and character approaches that can be applied in social studies to build anti-verbal bullying attitudes in students. In this study, the method used is literature study. Researchers collect data by searching for journals on Google Scholar. The results of the study from the collection of article data are then concluded by summarizing and determining the core of the results. The results of the study show that the phenomenon of verbal bullying has a significant impact on the development of students' character and the dynamics of social interaction in the educational environment. Social studies learning can be integrated effectively to instill anti-verbal bullying values through an approach that involves understanding social concepts, communication ethics and empathy. The learning methods and character approaches that can be applied in social studies subjects to build anti-verbal bullying attitudes among students are by using contextual and cooperative learning models.